Injective hydrogel encapsulating dental pulp stem cells for the treatment of traumatic optic nerve injury - Luo, Lihua; Xing, Zhenjie; Li, Yao; Wang, Ben; Dong, Na; Sun, Jiayi; Wang, Shuimiao; Xu, Yidi; He, Yan; Li, Lingli; Nan, Kaihui; Ye, Qingsong (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThe study aimed to evaluate the effect of GeLMA/bFGF hydrogel loaded with dental pulp stem cells (DPSCs) on the repair and regeneration of traumatic optic nerve injury.Materials and methodsGeLMA/bFGF hydrogel was photo-cross-linked by LED light. The physical–chemical properties and cytocompatibility of GeLMA/bFGF hydrogel after being squeezed (GeLMA/bFGF-SQ) were evaluated by SEM and degradation analyses, as well as live/dead and CCK-8 assays, respectively. The axon growth of PC12 cells was evaluated by MAP2 staining. The GeLMA/bFGF/DPSCs-SQ hydrogel was injected in situ into the lesion site to observe the repair of optic nerve injury. The number of retinal ganglion cells (RGCs) was calculated by βIII-tubulin staining. The length of regenerated axons was observed by CTB staining. Tissue recovery and axon growth of the optic nerve were observed by HE and TEM analyses, respectively.ResultsGeLMA/bFGF-SQ hydrogel had a porous structure and great degradability, as well as good cytocompatibility. Meanwhile, DPSCs-conditioned medium (DPSCs-CM) could promote the axon growth of PC12 cells. Moreover, the number of RGCs and the regeneration of axons of the optic nerve were the highest in the GeLMA/bFGF/DPSCs-SQ group. HE and TEM data revealed abundant newly and orderly arrangement of optic nerve axons that was observed in the damaged area of the GeLMA/bFGF/DPSCs-SQ group.ConclusionTransplantation of GeLMA/bFGF/DPSCs-SQ in situ provided an appropriate microenvironment for the repair and regeneration of injured optic nerves. Moreover, DPSCs combined with bFGF protected the RGCs from apoptosis and promoted optic nerve regeneration by secreting a series of neurotrophic factors.